2011
DOI: 10.1002/app.33817
|View full text |Cite
|
Sign up to set email alerts
|

Crack initiation and propagation in circular rubber bearings subjected to cyclic compression

Abstract: ABSTRACT:The fatigue failure mechanism of rubber bearings under cyclic compression is important in evaluating their fatigue lives and thus is analyzed theoretically and numerically here. At first, the stress distributions in a bonded rubber cylinder derived from three different existing models were utilized to calculate the cracking energy densities within it. Next, the location of fatigue crack initiation and the direction of subsequent crack propagation in circular rubber bearings were consecutively determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 18 publications
1
5
0
Order By: Relevance
“…The fatigue crack in bonded rubber cylinders thus initiates at the point with the maximum cracking energy density, and then propagates along the direction with the lowest cracking energy density. On the basis of Horton's theory, the curves which describe the crack initiation and propagation in bonded rubber cylinders with various shape factors under cyclic compression were determined, and these were also consistent with the experimental observations and the simulations of quasi‐static finite element numerical analyses 19. It is found that the fatigue cracks initiate at the outermost boundary ( r/R = 1) between rubber and steel plates and propagate inward to the center of circular rubber bearings.…”
Section: Theoretical Analysissupporting
confidence: 67%
See 4 more Smart Citations
“…The fatigue crack in bonded rubber cylinders thus initiates at the point with the maximum cracking energy density, and then propagates along the direction with the lowest cracking energy density. On the basis of Horton's theory, the curves which describe the crack initiation and propagation in bonded rubber cylinders with various shape factors under cyclic compression were determined, and these were also consistent with the experimental observations and the simulations of quasi‐static finite element numerical analyses 19. It is found that the fatigue cracks initiate at the outermost boundary ( r/R = 1) between rubber and steel plates and propagate inward to the center of circular rubber bearings.…”
Section: Theoretical Analysissupporting
confidence: 67%
“…To calculate the fatigue lives of circular rubber bearings, Chou and Huang 19 proposed a fatigue failure mechanism using a quasi statically numerical methods with three assumptions. First, intrinsic flaws with a uniform size distribute randomly in rubber.…”
Section: Theoretical Analysismentioning
confidence: 99%
See 3 more Smart Citations